Pendekatan Terhadap Islam Dalam Studi Agama : ( Problem Insider dan Outsider dalam Pandangan Muhammad Abdul Rauf dan Fazlur Rahman ) - Isfihani, Isfihani (Sanaamul Quran: Jurnal Wawasan Keislaman, 2024)
One prominent issue in contemporary Islamic Studies discourse is the adaptation of methodologies and epistemologies that have significantly evolved, causing themes in Islamic Studies to be perceived as rigid and static due to not keeping pace with contemporary scientific developments. The controversy surrounding the adoption of these methodologies generally divides the Islamic community into two opinions. The first opinion suggests that the current lag in the Islamic community is not due to a lack of responsiveness or adaptability to various scientific-philosophical-academic advancements. Instead, it asserts that the lag is a result of Muslims abandoning their rich intellectual and scientific heritage. Therefore, the proposed solution to revive the Islamic community from its decline is through a "back to the past" approach, retracing the steps of the classical Islamic scientific civilization that once flourished. This viewpoint is represented by Muhammad Abdul Rauf. On the other hand, the second opinion contends that the adaptation of methodologies is imperative if the Islamic community is to avoid falling behind in the competition of scientific-philosophical-academic discourse, which has implications for the rapid growth of civilization with the scientific-philosophical-academic world as its axis. This perspective is represented by Fazlur Rahman.